2016
DOI: 10.1021/acs.jmedchem.5b01517
|View full text |Cite
|
Sign up to set email alerts
|

Aminothiazoles as Potent and Selective Sirt2 Inhibitors: A Structure–Activity Relationship Study

Abstract: Sirtuins are NAD + -dependent protein deacylases that cleave off acetyl, but also other acyl groups from the ε-amino group of lysines in histones and other substrate proteins.Dysregulation of human Sirt2 (hSirt2) activity has been associated with the pathogenesis of cancer, inflammation, and neurodegeneration, which makes the modulation of hSirt2 activity a promising strategy for pharmaceutical intervention. The Sirtuin Rearranging Ligands (SirReals) have recently been discovered by us as highly potent and iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 85 publications
(85 citation statements)
references
References 65 publications
3
81
0
1
Order By: Relevance
“…), with improved biological activities in vitro and in cells. Furthermore, a well‐defined structure–activity model was established by extensive inhibitor syntheses and biological testing . Using the detailed SARs and the obtained structural knowledge, a highly active and selective affinity probe for Sirt2 was developed.…”
Section: Small‐molecule Inhibitors Of Sirtuinsmentioning
confidence: 99%
See 1 more Smart Citation
“…), with improved biological activities in vitro and in cells. Furthermore, a well‐defined structure–activity model was established by extensive inhibitor syntheses and biological testing . Using the detailed SARs and the obtained structural knowledge, a highly active and selective affinity probe for Sirt2 was developed.…”
Section: Small‐molecule Inhibitors Of Sirtuinsmentioning
confidence: 99%
“…D and E). The dimethylpyrimidine part of the inhibitors interacts with the “selectivity pocket.” Chemical optimization resulted in analogs with higher potency . The derived crystal structures showed that additional hydrophobic contacts and further H‐bonds with Arg97 can explain the improved inhibitory activity.…”
Section: Structural Insights Into Sirtuins and Sirtuin‐modulator Compmentioning
confidence: 99%
“…Protein preparation of different crystal structures of human sirt1 (PDB IDs: 4I5I [44], and 4ZZJ [45]), was carried out as detailed in the Supplementary Material, while sirt2 protein structures were prepared as previously described [36] (details in Supplementary Material). The docking procedure was performed using GOLD program (The Cambridge Crystallographic Data Centre, CCDC, Cambridge, UK) [60][61][62], preceded by preparation of the ligands using the LigPrep (Schrödinger, LLC, New York, NY, 2014) [55] tool in Maestro (Schrödinger, LLC, New York, NY, 2014) [61].…”
Section: Protein Preparationmentioning
confidence: 99%
“…In the crystal structures of sirt1, it was shown that substrates make H-bond interactions with the backbone of a conserved valine residue (sirt1 numbering Val412) which is crucial for the correct orientation of the acyl-lysine in the active site [44]. In case of sirt2, we first examined the binding interactions of the native ligands including both the peptide substrates, the cofactor fragments and the co-crystallized inhibitors with the protein [31][32][33][34][35][36][37][38][39][40][41][42][43]. In the hit selection process, a special importance was given to compounds that were able to interact with residues Phe234, Phe235, Phe190 and Glu237 in the catalytic pocket.…”
Section: Docking Scoring and Hit Selectionmentioning
confidence: 99%
See 1 more Smart Citation